Real-time measurement of dynamic film thickness via ultrasonic technology - Peng Liang; Lingsheng Kong; Feng Guo; Wei Sun; Fulin Jiang (Friction)
When the lubricating film between friction pairs is too thin, severe wear can occur. Ultrasonic technology is nondestructive and has strong penetrability in the field of film thickness measurement. However, real-time systems for measuring film thickness with ultrasonic technology have rarely been researched. This study proposes a real-time measuring system and performs online measurements of four kinds of dynamically changing film thicknesses. A new method for selecting the probe model is proposed, and this method uses an effective bandwidth as a “connecting bridge” between the target film thickness and the probe model. Little is known about the measurement failure zone between the measurement ranges of the spring model and the resonance model, and this study develops an understanding of the influence of the material and thickness of the friction pair on the measurement failure zone. When the friction pair thickness exceeds 30 mm, the “vacuum zone” of the film thickness measurement begins to appear. To measure the film thickness in the failure zone, a composite model using both the phase and amplitude of the reflection coefficient is proposed. Finally, the present work constructs a physical model for ultrasonic measurement experiments. This study provides a method for monitoring the lubrication and friction status of important rotating parts of mechanical equipment in real time.